Pradefovir: A Prodrug That Targets Adefovir to the Liver for the Treatment of Hepatitis B - Reddy, K. Raja; Matelich, Michael C; Ugarkar, Bheemarao G; Gómez-Galeno, Jorge E; DaRe, Jay; Ollis, Kristin; Sun, Zhili; Craigo, William; Colby, Timothy J; Fujitaki, James M; Boyer, Serge H; van Poelje, Paul D; et al. (Journal of medicinal chemistry, 2008)
Adefovir dipivoxil, a marketed drug for the treatment of hepatitis B, is dosed at submaximally efficacious doses because of renal toxicity. In an effort to improve the therapeutic index of adefovir, 1-aryl-1,3-propanyl prodrugs were synthesized with the rationale that this selectively liver-activated prodrug class would enhance liver levels of the active metabolite adefovir diphosphate (ADV-DP) and/or decrease kidney exposure. The lead prodrug (14, MB06866, pradefovir), identified from a variety of in vitro and in vivo assays, exhibited good oral bioavailability (F = 42%, mesylate salt, rat) and rate of prodrug conversion to ADV-DP. Tissue distribution studies in the rat using radiolabeled materials showed that cyclic 1-aryl-1,3-propanyl prodrugs enhance the delivery of adefovir and its metabolites to the liver, with pradefovir exhibiting a 12-fold improvement in the liver/kidney ratio over adefovir dipivoxil.